THE INCOME TAX FROM EXCESS OF VAT ON THE SALE OF USED MOTOR VEHICLES - Waidatin Nur Azizah (Jurnal Pajak dan Keuangan Negara (PKN), 2021)
Sales of used motor vehicles in Indonesia are subject to Value Added Tax (VAT) of 10% of the selling price and are charged to consumers. Value-Added Taxes collected when delivering to consumers are called output taxes. According to PMK Number 79 of 2010, Taxable Entrepreneurs (PKP) who sell retail used motor vehicles credit and input tax of 90% of the output tax. Therefore, PKP remits the payable VAT to the state treasury at 1% of the selling price. As a result, there is a more difference of 9% of the selling price paid by consumers and not deposited in the national treasury. According to research, this 9% excess is income for entrepreneurs and may be subject to income tax. However, no regulations are governing further regarding the taxation of this excess. The purpose of this study is to determine the potential income tax on the excess of VAT on the sale of motorcycles and used car retail. The research method used is descriptive qualitative using primary data and secondary data. Primary data is obtained directly from data sources, namely in-depth interviews with practitioners and academics in taxation at the Fiscal Policy Agency and the Directorate General of Taxation. The results of this study are that there is considerable potential regarding aspects of income tax on the excess of VAT on retail sales of used motorcycles and cars